Effectors of thioredoxin reductase: Brevetoxins and manumycin-A - Tuladhar, Anupama (Comp Biochem Physiol C Toxicol Pharmacol, 2018)
The activities of two effectors, brevetoxin (PbTx) and manumycin-A (Man-A), of thioredoxin reductase (TrxR) have been evaluated against a series of fourteen TrxR orthologs originating from mammals, insects and protists and several mutants. Man-A, a molecule with numerous electrophilic sites, forms a covalent adduct with most selenocystine (Sec)-containing TrxR enzymes. The evidence also demonstrates that Man-A can form covalent adducts with some non-Sec-containing enzymes. The activities of TrxR enzymes towards various substrates are moderated by Man-A either positively or negatively depending on the enzyme. In general, the reduction of substrates by Sec-containing TrxR is inhibited and NADPH oxidase activity is activated. For non-Sec-containing TrxR the effect of Man-A on the reduction of substrates is variable, but NADPH oxidase activity can be activated even in the absence of covalent modification of TrxR. The effect of PbTx is less pronounced. A smaller subset of enzymes is affected by PbTx. With a single exception, the activities of most of this subset are activated. Although both PbTx variants can react with selenocytine, a stable covalent adduct is not formed with any of the TrxR enzymes. The key findings from this work are (i) the identification of an alternate mechanism of toxicity for the algal toxin brevetoxin (ii) the demonstration that covalent modification of TrxR is not a prerequisite for the activation of NADPH oxidase activity of TrxR and (iii) the identification of an inhibitor which can discriminate between cytosolic and mitochondrial TrxR.